Differential Brain MicroRNA Expression Profiles After Acute and Chronic Infection of Mice With Toxoplasma gondii Oocysts - Hu, Rui-Si; He, Jun-Jun; Elsheikha, Hany M.; Zhang, Fu-Kai; Zou, Yang; Zhao, Guang-Hui; Cong, Wei; Zhu, Xing-Quan (Frontiers in Microbiology, 2018)
Brain microRNAs (miRNAs) change in abundance in response to Toxoplasma gondii infection. However, their precise role in the pathogenesis of cerebral infection with T. gondii oocyst remains unclear. We studied the abundance of miRNAs in the brain of mice on days 11 and 33 post-infection (dpi) in order to identify miRNA pattern specific to early (11 dpi) and late (33 dpi) T. gondii infection. Mice were challenged with T. gondii oocysts (Type II strain) and on 11 and 33 dpi, the expression of miRNAs in mouse brain was investigated using small RNA (sRNA) sequencing. miRNA expression was confirmed by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases were used to identify the biological processes, molecular functions, and cellular components, as well as pathways involved in infection. More than 1,500 miRNAs (1,352 known and 150 novel miRNAs) were detected in the infected and control mice. The expression of miRNAs varied across time after infection; 3, 38 and 108 differentially expressed miRNAs (P < 0.05) were detected during acute infection, chronic infection and chronic versus acute infection, respectively. GO analysis showed that chronically infected mice had more predicted targets of dysregulated miRNAs than acutely infected mice. KEGG analysis indicated that most predicted targets were involved in immune- or disease-related pathways. Our data indicate that T. gondii infection alters the abundance of miRNAs in mouse brain particularly at the chronic stage, probably to fine-tune conditions required for the establishment of a latent brain infection.